LIBERALISASI MASYARAKAT EKONOMI ASEAN 2015: APAKAH KITA PERLU HUKUM PIDANA EKONOMI? (LIBERALIZATION AEC 2015: DO WE NEED ECONOMIC CRIMINAL LAW?) - Hamzah Hatrik (Supremasi Hukum: Jurnal Penelitian Hukum, 2015)
ABSTRACTThe liberalization ofthe Asean Economic Community is a process of economic integration free way to apply the principles of an open economy and market oriented. Liberal economic characteristics such as the free flow of goods, free flow of services, free flow of investment, free flow of capital, and the free flow of skilled labor indicate increasing role of corporations. Based on the reality of the negative impacts of corporate activities to maximize profit without limits, then the economics of criminal law is useful to anticipate corporate crime. To improve the functioning ofthe economic criminal law, then the Criminal Code (ius contituendum) there should be special arrangement of corporate criminal liability as a legal person. Based on the proposed conceptual study conclusions and suggestions for formulating the basic corporate criminal sanctions: the lifting of the deed; revocation of business license; restitution; and fines. While the additional punishment: pecabutan certain rights; deprivation of certaingoods; and publication of the decision of the judge.  Keywords: liberalization, economic, corporate, criminal law.ABSTRAKLiberalisasi Masyarakat Ekonomi Asean merupakan proses integrasi ekonomi bebas hambatan untuk menerapkan prinsip ekonomi terbuka dan berorientasi pada pasar. Karakteristik ekonomi liberal seperti aliran bebas barang, aliran bebas jasa, aliran bebas investasi, aliran modal yang lebih bebas, dan aliran bebas tenaga kerja terampil mengindikasikan peran korporasi makin meningkat. Berdasarkan realitas dampak negatif aktivitas korporasi memaksimalkan profit tanpa batas, maka hukum pidana ekonomi berguna untuk mengantisipasi kejahatan korporat. Untuk meningkatkan fungsi hukum pidana ekonomi, maka dalam KUHP (ius contituendum) harus ada pengaturan khusus tanggung jawab pidana korporasi sebagai person hukum. Berdasarkan kajian konseptual diajukan simpulan dan saran untuk merumuskan sanksi pidana pokok korporasi: pencabutan akta; pencabutan izin usaha; restitusi; dan denda. Sedangkan pidana tambahan: pecabutan hak tertentu; perampasan barang tertentu; dan publikasi putusan hakim. Kata Kunci: liberalisasi, ekonomi, korporasi, hukum pidana.